Role of Glutamatergic Projections from Ventral Tegmental Area to Lateral Habenula in Aversive Conditioning - Root, David H. (Society for Neuroscience, 2014)
The ventral tegmental area (VTA) plays roles in both reward and aversion. The participation of VTA in diverse behaviors likely reflects its heterogeneous neuronal phenotypes and circuits. Recent findings indicate that VTA GABAergic neurons that coexpress tyrosine hydroxylase (TH) projecting to lateral habenula (LHb) play a role in reward. In addition to these mesohabenular TH-GABAergic neurons, the VTA has many neurons expressing vesicular glutamate transporter 2 (VGluT2) that also project to LHb. To determine the behavioral role of mesohabenular VGluT2 neurons, we targeted channelrhodopsin2 to VTA VGluT2 neurons of VGluT2::Cre mice. These mice were tested in an apparatus where moving into one chamber stimulated VTA VGluT2 projections within the LHb, and exiting the chamber inactivated the stimulation. We found that mice spent significantly less time in the chamber where VGluT2 mesohabenular fiber stimulation occurred. Mice that received injections of mixed AMPA and NMDA glutamate receptor antagonists in LHb were unresponsive to VGluT2-mesohabenular fiber stimulation, demonstrating the participation of LHb glutamate receptors in mesohabenular stimulation-elicited aversion. In the absence of light stimulation, mice showed a conditioned place aversion to the chamber that was previously associated with VGluT2-mesohabenular fiber stimulation. We conclude that there is a glutamatergic signal from VTA VGluT2-mesohabenular neurons that plays a role in aversion by activating LHb glutamatergic receptors.